Source analysis of heavy metal elements of PM2.5 in canteen in a university in winter. (1st January 2021) - Niu, Yuanyuan; Wang, Fang; Liu, Songmin; Zhang, Wenjie
Abstract: Indoor air particulate samples were collected in the first floor of the Xingyuan canteen of Nanjing University of Science and Technology (NJUST) in Nanjing during the winter season. Meanwhile, outdoor air particulate samples were collected on the roof of a building that is 28 m away from the canteen. The mean PM2.5 (fine particulate matter) concentrations of the indoor and outdoor samples were found to be 99.43 and 103.09 μg/m 3, respectively. Through correlation analysis, it was found that more than half of the PM2.5 penetrates from the adjacent outdoor area into the canteen. Inductively coupled plasma optical emission spectrometry (ICP-OES) was used to determine the concentration of heavy metals (As, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Zn) in the PM2.5, revealing that the concentration of As, Mn and Cd in the canteen exceeded health standards. Positive Matrix Factorization (PMF) was used to identify the pollution sources of the PM2.5 -related heavy metals in the canteen, revealing the following sources in descending order: cooking (34.7%), fuel combustion (28.9%), canteen kitchenware (14.4%), transportation (9.6%), indoor building materials (8%) and the Earth's crust (4.4%). Enrichment factor analysis revealed the source of the excessive As in the canteen to be the outdoor air and the cooking of a large amount of meat in the canteen. The outdoor air contained excessive As and infiltrated the canteen. In addition, the Earth's crust was found to be the source of excessive Mn in the canteen, while transportation was the cause of excessive Cd. Highlights: This study used EPA PMF 5.0 (USEPA, 2014) to analyse the sources of PM2.5 related heavy metals in the air. The sources of PM2.5 related heavy metals in canteen of university in winter are as follows, in descending order: cooking source (34.7%), fuel combustion source (28.9%), canteen kitchenware source (14.4%), transportation source (9.6%), indoor building materials source (8%) and crustal source (4.4%). As, Mn and Cd exceed the standard seriously in the canteen of university. The reason of excessive As in canteen the outdoor air containing excessive As infiltrates into the canteen and the cooking of a large amount of meat in the canteen.